Impacts of Prisons in Rural Communities: Economic and Social Factors - Rasheed, Ashleigh T (2016)
Rural communities in the United States have been declining economically for the past four decades. Some local government officials have seen prisons as a golden opportunity to revitalize their economies. Why and how do local officials decide to invest in prisons? What process do local officials go through to decide to invest in prisons? What are the economic impacts associated with a prison siting? What effects do stigmas associated with prisons have on the residents living in the community? I argue that prisons provide a short term economic gain for rural communities by providing jobs for the residents, thus boosting the economy. I also argue that over time the economy will reach a plateau and start to decline as result of the stigmas associated with the prison siting. I will test this argument using quantitative analysis of national prison data and I will also test this argument using qualitative analysis of an original single case study of Millen, Georgia